Effects of Chemical Fertilizer, Fym and Bio-Inoculants On Nutrient Content, Uptake and Quality of Wheat (Triticum Aestivum L.) (Bangladesh Journal of Botany, 2021)
Effects of different levels of chemical fertilizer, farmyard manure (FYM) and bio-inoculants on nutrient content, uptake and quality parameter of wheat were studied. Results indicated that increasing levels of chemical fertilizer, FYM and bio-inoculants significantly enhanced nutrient content and uptake by wheat, while quality parameters of wheat showed significant results with bio-inoculants application. Maximum N, P and K content and their uptake in grain (80.3, 11.07 and 25.29%, respectively) and straw (32.18, 7.14 and 95.92%, respectively) were noticed with 100% NPK over control. Application of FYM @ 10 t/ha significantly increased nutrient content (NPK) in grain and straw and their uptake over the control. The total N, P and K uptake by wheat were found to be maximum 80.97, 12.68 and 86.10 kg/ha, respectively with the application of FYM over control. Combined use of fertilizer levels and FYM, and combined use of fertilizer levels and bio-inoculants significantly increased the nutrient uptake by wheat.Bangladesh J. Bot. 50(4): 1109-1117, 2021 (December)